Depolymerization and Nanoliposomal Encapsulation of Grape Seed Condensed Tannins: Physicochemical Characterization, Stability, in Vitro Release and Bioaccessibility - Osorio-Lira, F (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Condensed tannins from grape seed residues show high antioxidant activity but low oral bioavailability because of their high degree of polymerization and covalent interactions with proteins. This study aimed to improve their bioaccessibility through depolymerization and encapsulation. Depolymerization was carried out using microwave-assisted SN1 reactions with gallic acid as a nucleophile under food-grade conditions, mainly producing epicatechin monomers with 99.8% polymer degradation efficiency. Importantly, the inhibition of ABTS●+ and DPPH● radicals remained unaffected (p > 0.05), indicating that depolymerization preserved the antioxidants’ redox function, maintaining about 90% of their inhibition activity. The products were encapsulated in phosphatidylcholine liposomes, which had nanometric sizes and high encapsulation efficiency (83.11%), and remained stable for up to 60 days. In vitro release of nanoliposomal epicatechin in a D1 simulant was less than 10% after 48 h, fitting a Weibull model (β = 0.07), suggesting sub-diffusive transport and demonstrating high bioactive retention capacity in aqueous systems. During in vitro digestion, bioaccessibility of gallic acid and epicatechin reached 95.61 ± 0.58% and 98.56 ± 0.81%, respectively, with a 2333% increase in the bioaccessible mass of flavan-3-ols in native liposomal condensed tannins, which otherwise showed no detectable bioaccessibility. These findings highlight the potential of polyphenols from agro-industrial waste with enhanced bioaccessibility for applications in nutraceuticals and functional foods. © 2025 by the authors.